Remote Monitoring System for Electricity Meter Using ESP32CAM and OCR Analysis using MATLAB - Mochammad Shaleh, Mochammad Safii; Chia, Kim Seng (Evolution in Electrical and Electronic Engineering, 2024)
The increasing demand for effective and intelligent energy management systems has prompted the advancement of sophisticated technologies for the real-time monitoring of electricity usage. This study introduces a Remote Monitoring System that utilizes the ESP32CAM microcontroller and employs Optical Character Recognition (OCR) analysis to offer a comprehensive solution for remotely monitoring electricity meters. The system utilizes the ESP32CAM microcontroller, known for its power and versatility, to capture periodic images of electricity meters. Subsequently, OCR analysis is applied to extract numerical data, such as meter readings, from the captured images, enhancing automation and accuracy while minimizing manual intervention. Key elements of the proposed system encompass an ESP32CAM module equipped with a camera for image capture, integrated wireless connectivity for remote communication, and OCR algorithms for efficient data extraction. The system is designed to be adaptable, accommodating various types of electricity meters commonly found in residential, commercial, and industrial settings. The capabilities of remote monitoring empower users to access real-time data on electricity consumption through a user-friendly interface, facilitating informed decisions regarding energy management. Moreover, the system has the potential for proactive maintenance by notifying users of irregularities or anomalies in electricity consumption patterns. The suggested Remote Monitoring System offers a cost-effective and scalable solution to enhance the efficiency of electricity consumption monitoring. By amalgamating the features of ESP32CAM and OCR analysis, this system establishes a dependable platform for remote monitoring, contributing to the progression of intelligent and sustainable energy management practices.